Addressing Rape Culture through Folktale Adaptation in Malaysian Young Adult Literature. Issue 1 (1st March 2021) - Osman, Sharifah Aishah
Abstract: Rape culture is a provocative topic in Malaysia; the public discourse on it is plagued by gender stereotyping, sexism, misogyny, and rape myths. Recent literary works aimed at Malaysian adolescent girls have interrogated rape culture more pointedly as a means of addressing gender-based violence through activism and education. In this article, I discuss two short stories, "The Girl on the Mountain" and "Gamble" as retellings of Malaysian legends and feminist responses to the normalization and perpetuation of rape culture in this society. Through the emphasis on female agency, consent, and gender equality, these two stories reflect the subversive power of Malaysian young adult literature in dismantling rape culture, while affirming the significance of the folktale as an empowering tool for community engagement and feminist activism.